The life-changing magic of tidying up : the Japanese art of decluttering and organizing - Kond, Marie; Hirano, Cathy (Berkeley, California : Ten Speed Press, 2014)
This best-selling guide to decluttering your home from Japanese cleaning consultant Marie Kondo takes readers step-by-step through her revolutionary KonMari Method for simplifying, organizing, and storing.
Why can't I keep my house in order? -- Finish discarding first -- Tidying by category works like magic -- Storing your things to make your life shine -- The magic of tidying dramatically transforms your life.
Translation of: Jinsei ga tokimeku katazuke no mah.
This translation first published: Great Britain : Ebury, 2014.
Includes index.
Keywords: Housekeeping; Home economics